Indikator Adaptasi Masyarakat Terhadap Krisis Air (Studi Kasus di Palu’e, NTT dan Kembangbahu, Jawa Timur) - Putri R., Ratih (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2014)
When climate began to change, water resources are the most affected sectors. Of all the consequences of climate change, the biggest impact is on hydrological cycle and water resources management and social-economic system. Social and economic condition of the community is very influential on the adaptation of society. Adaptive capacity is characterized by the ability of communities to adapt to the changes occuring. This study aims to determine correlation between the willingness to pay and the indicators of education, income, and distance to water sources in Palu’e, NTT and Kembangbahu, East Java. Chi-square analysis method was used to analyze questionnaire result from 46 respondents in Kembangbahu and 28 respondents in Palu’e. The calculation result shows that the three adaptation indicators do not have a correlation with the willingness to pay. This variable indicates the level of adaptation. However, local wisdom significantly affects the adaptation of society.